2017
DOI: 10.1038/ismej.2017.134
|View full text |Cite
|
Sign up to set email alerts
|

Feathermoss and epiphytic Nostoc cooperate differently: expanding the spectrum of plant–cyanobacteria symbiosis

Abstract: Dinitrogen (N2)-fixation by cyanobacteria in symbiosis with feathermosses is the primary pathway of biological nitrogen (N) input into boreal forests. Despite its significance, little is known about the cyanobacterial gene repertoire and regulatory rewiring needed for the establishment and maintenance of the symbiosis. To determine gene acquisitions and regulatory changes allowing cyanobacteria to form and maintain this symbiosis, we compared genomically closely related symbiotic-competent and -incompetent Nos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(111 citation statements)
references
References 49 publications
7
103
1
Order By: Relevance
“…However, it is also possible that WPS‐2 could be capable of sulfide‐based anoxygenic phototrophy by obtaining sulfur from organic compounds provided by the moss, as was proposed by Warshan et al . () for interactions between feather mosses and their Cyanobacteria . If WPS‐2 is an AAP or a FAP, it would be one of the few observed lineages to possess RuBisCo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that WPS‐2 could be capable of sulfide‐based anoxygenic phototrophy by obtaining sulfur from organic compounds provided by the moss, as was proposed by Warshan et al . () for interactions between feather mosses and their Cyanobacteria . If WPS‐2 is an AAP or a FAP, it would be one of the few observed lineages to possess RuBisCo.…”
Section: Resultsmentioning
confidence: 99%
“…Neither FAPs nor AAPs depend on sulfur for growth and both have the potential to survive in aerobic or microaerobic conditions, though FAPs cannot grow photoautotrophically in fully aerobic conditions (Madigan et al, 2017;Yurkov and Hughes, 2017). However, it is also possible that WPS-2 could be capable of sulfide-based anoxygenic phototrophy by obtaining sulfur from organic compounds provided by the moss, as was proposed by Warshan et al (2017) for interactions between feather mosses and their Cyanobacteria. If WPS-2 is an AAP or a FAP, it would be one of the few observed lineages to possess RuBisCo.…”
Section: Draft Genome Of Wps-2 Recovered From Metagenomic Datamentioning
confidence: 98%
“…These symbiotic cyanobacteria can enter epiphytic and intracellular or extracellular endophytic interactions with their host. In boreal forests, this N 2 fixation by cyanobacteria living in symbiosis with mosses can account to up to 50% of total biological N input (DeLuca, Zackrisson, Nilsson, & Sellstedt, ; Santi et al, ; Warshan et al, ). In N‐depleted soils in Mexico, recent work has shown that the mucilage of aerial roots of an indigenous landrace of maize enriched in diazotrophs (Van Deynze et al, ) (Figure ).…”
Section: Plants Acquire Nitrogen By Recruiting Micro‐organisms Througmentioning
confidence: 99%
“…These symbiotic cyanobacteria can enter epiphytic and intracellular or extracellular endophytic interactions with their host. In boreal forests, this N 2 fixation by cyanobacteria living in symbiosis with mosses can account to up to 50% of total biological N input (DeLuca, Zackrisson, Nilsson, & Sellstedt, 2002;Santi et al, 2013;Warshan et al, 2017).…”
Section: Pl Ants Acqu Ire Nitrog En By Recruiting Micro -Org Anis Mmentioning
confidence: 99%
“…4). Although the mechanisms for N transfer from these N-fixing bacteria to mosses (Warshan et al, 2017) remain to be fully characterized, fungi might take advantage of the mossbacteria association to obtain nitrogen. Fungi-bacteria-moss interactions appear to be complex and might involve other organisms, such as arthropod and algae that also inhabit mosses (Andrew et al, 2003;Knapp and Lowe, 2009;Feng et al, 2016).…”
Section: Ammonium Versus Nitrate Transport By Fungimentioning
confidence: 99%